Occurrence and antimicrobial resistance of Salmonella serotypes isolated from chicken carcasses in Duhok, Kurdistan Region / Iraq - A.Taha, Zanan M.; Ahmed, Meqdad S.; Abdo, Jassim M. (Sulaimani Journal for Pure and Applied Sciences, 2015)
This study was undertaken to evaluate the contamination rate of Salmonella serotypes and to determine their resistance profiling to six antibiotics from imported chicken carcass surfaces at the food control unit in the Duhok city / Ministry of Health, Kurdistan region of Iraq. in which the total 110 swabs were collected from April to June 2014. 21 samples out of 110 (19%) chickens were found to be contaminated with Salmonella and belonging to 4 different serotypes. S. ohio 13 (61.9%) was the most frequent serotype followed by S.newport 2 (9.5%), S.typhimurium 2 (9.5%), S.livingstone 1 (4.7%) and 3 (14.2%) isolates were non-typeable. 23.8% of the isolates were resistant to ciprofloxacin, 100% to cephalothin, 85.7% to trimethoprim-sulfamethoxazole, 28.5% to gentamycin, 76.1% ticarcillin-calvulanic acid while none of the isolates were resistant to imipenem (100% were susceptible). All Salmonella serotypes were resistant to at least one antibiotic and 16 (76.1%) have been resistant to three or more antibiotics. The results of this study indicate that there are high contamination rate of Salmonella in chicken carcasses with a high drug resistance profiling and require good strategies for controlling the pathogen during slaughtering. In addition, the selection of antibiotics should be with a more prudent
Keywords: Salmonella; chicken carcasses; antimicrobial resistance; molecular identification Correspondence